Public engagement, historians and higher education: A retrospective UK case study - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2015)
Focussing on the practice of public engagement and the teaching of history in higher education, this article will argue that public engagement is a welcome platform for sustaining humanities education through the economic stagnation and educational changes that have impacted Europe in the early 21st century. However, effective public engagement is becoming an increasingly important practice that universities are implementing all over the globe. Based on a case study of a course module run at a UK university for final-year undergraduates, this article proposes a practical framework for humanities departments to embed public engagement into departmental teaching programmes. It will demonstrate from the real-life experiences of staff and students engaged on a pilot programme how humanities subjects can also be practical skills-based learning experiences. The first section will review the current field of public engagement practice and methodology and explore why the subject has received much more attention over recent years, particularly within a UK context. The second section examines the case study itself, which was conducted during the 2009–10 academic year. The concluding section provides reflection and considers the possibilities for adopting a public engagement initiative within humanities departments in the future.